2020
DOI: 10.1186/s43088-020-00087-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of seaweed (Ulva lactuca) and Azolla on growth performance, haematological and serum biochemical parameters of Aseel chicken

Abstract: Background An effort was made to assess the effectiveness of dietary supplementation of Ulva lactuca (U. lactuca), a seaweed and Azolla individually and in combination on different physiological parameters of Aseel chicken. A total of 40 Aseel chicks of 8 weeks old were allocated into four groups, C1 (control), T1 (Azolla alone), T2 (seaweed alone) and T3 (seaweed plus Azolla). Aseel chicks in C1 were fed with formulated grower feed alone, birds in T1 had control diet with 5% Azolla, birds in T2 had control di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…Between the treatment groups the birds in T2 group showed higher growth convertibility than in the group T1 having supplemented with brown sea weed the S. wightii. Although the brown sea weed contained a range of bioactive compounds, it was proved to have lower nutritional value when compared to the red and green sea weeds (Misurcova 2011;Vijayalingam et al, 2020). The proximate analysis in the present study also showed a higher total protein, higher gross energy and lower fiber content in the red sea weed, G. corticatta when compared to the brown sea weed.…”
Section: Growth Performancesupporting
confidence: 39%
See 3 more Smart Citations
“…Between the treatment groups the birds in T2 group showed higher growth convertibility than in the group T1 having supplemented with brown sea weed the S. wightii. Although the brown sea weed contained a range of bioactive compounds, it was proved to have lower nutritional value when compared to the red and green sea weeds (Misurcova 2011;Vijayalingam et al, 2020). The proximate analysis in the present study also showed a higher total protein, higher gross energy and lower fiber content in the red sea weed, G. corticatta when compared to the brown sea weed.…”
Section: Growth Performancesupporting
confidence: 39%
“…M odern intensive poultry production has achieved phenomenal gains in the efficient and economical production of high quality and safe chicken meat, eggs and poultry bio-products (Vijayalingam et al, 2020). At the same time as making gains in production and efficiency, the industry has to maximise the health and well-being of the birds with minimal expenditure (Holdt and Kraan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chan et al [ 23 ] showed that trilinolein exhibits an antioxidant effect. The antioxidant effect may also be credited to antioxidants and immune-boosting phytocontents (vitamins and phytochemicals including carotenoids, flavonoids, and tannins) [ 24 ]. Azolla’s high carotene, phenolic, and flavonoid contents are also credited for its immune-enhancing effects [ 25 ].…”
Section: Discussionmentioning
confidence: 99%